Validation of the COVID-19 Indoor Test™ by Phylagen for Detection of SARS-CoV-2 Virus on Stainless-Steel Surfaces: AOAC Performance Tested MethodSM 122004. (2nd April 2021) - Fantin, Nick; Taft, Brad; Ugalde, Juan; Spring, Katie; Lam, Hannah; Tran, Alex; Green, Jessica
Abstract: Background: The COVID-19 Indoor Test™ by Phylagen uses a real-time PCR Assay to detect nucleic acid from SARS-CoV-2, the causative agent of COVID-19, which is extracted from swabs sampled from environmental surfaces. This information can be used to detect the presence of the virus in indoor environments. Objective: To validate the COVID-19 Indoor Test TM by Phylagen as part of the AOAC Research Institute's Emergency Response Validation Performance Tested Method(s) SM program. Method: The COVID-19 Indoor Test by Phylagen assay was evaluated for specificity using in silico analysis of 15 764 SARS-CoV-2 sequences and 65 exclusivity organisms. The candidate method was also evaluated in an unpaired matrix study design for one environmental surface (stainless steel) and compared to the U.S. Centers for Disease Control and Prevention 2019-Novel Coronavirus (2019-nCoV) Real-Time RT-PCR Diagnostic Panel (Revision 4, Effective 6/12/2020). Results: Results of the in silico analysis demonstrated the specificity of the method in being able to detect SARS-CoV-2 target sequences and discriminate them from near-neighbors. In the matrix study, the candidate method demonstrated statistically significant better recovery of the target analyte than the reference method (2 × 10 3 GU/2 × 2" test surface). Conclusions: The COVID-19 Indoor Test by Phylagen is a rapid and accurate method that can be utilized to monitor the presence of SARS-CoV-2, the causative agent of COVID-19, on stainless-steel surfaces in built environments. Highlights: The COVID-19 Indoor Test by Phylagen assay performed significantly better than the reference method when used to detect SARS-CoV-2 from environmental surfaces.